À propos des inondations récentes de la région de l’Aiguillon-sur-Mer, en Vendée - Fernand Verger (EchoGéo)
On February 28th 2010, the storm Xynthia occurred during high water spring tide. The conjunction of severe meteorological conditions andhigh sea level caused a very large flooding on the South coast of Vendée. The storm swamped several thousand hectares and killed many people.